Remodeling‐ and Modeling‐Based Bone Formation With Teriparatide Versus Denosumab: A Longitudinal Analysis From Baseline to 3 Months in the AVA Study. (15th November 2017) - Dempster, David W; Zhou, Hua; Recker, Robert R; Brown, Jacques P; Recknor, Christopher P; Lewiecki, E Michael; Miller, Paul D; Rao, Sudhaker D; Kendler, David L; Lindsay, Robert; Krege, John H; Alam, Jahangir; et al.
ABSTRACT: There has been renewed interest of late in the role of modeling‐based formation (MBF) during osteoporosis therapy. Here we describe early effects of an established anabolic (teriparatide) versus antiresorptive (denosumab) agent on remodeling‐based formation (RBF), MBF, and overflow MBF (oMBF) in human transiliac bone biopsies. Postmenopausal women with osteoporosis received subcutaneous teriparatide ( n  = 33, 20 μg/d) or denosumab ( n  = 36, 60 mg once/6 months), open‐label for 6 months at 7 US and Canadian sites. Subjects received double fluorochrome labeling at baseline and before biopsy at 3 months. Sites of bone formation were designated as MBF if the underlying cement line was smooth, RBF if scalloped, and oMBF if formed over smooth cement lines adjacent to scalloped reversal lines. At baseline, mean RBF/bone surface (BS), MBF/BS, and oMBF/BS were similar between the teriparatide and denosumab groups in each bone envelope assessed (cancellous, endocortical, periosteal). All types of formation significantly increased from baseline in the cancellous and endocortical envelopes (differences p  < 0.001) with teriparatide (range of changes 2.9‐ to 21.9‐fold), as did MBF in the periosteum ( p  < 0.001). In contrast, all types of formation were decreased or not significantly changed with denosumab, except MBF/BS in the cancellous envelope, which increased 2.5‐fold (difference p  = 0.048). These data highlight mechanistic differences between these agents: all 3 types of bone formation increased significantly with teriparatide, whereas formation was predominantly decreased or not significantly changed with denosumab, except for a slight increase in MBF/BS in the cancellous envelope. © 2017 American Society for Bone and Mineral Research.